Perlindungan Hukum Terhadap Konsumen Atas Barang Yang Tidak Sesuai Dalam Perjanjian Jual Beli Melalui Transaksi Online - Maulana, Rizky; Ansari, Teuku Syahrul (Jurnal Ilmiah Wahana Pendidikan, 2024)
E-commerce, commonly known as online shopping, is an indirect transaction process facilitated through the internet and various digital platforms, allowing users to purchase or sell products and services. This involves the use of intermediary applications, and customers can directly buy goods or services. The focus of this research is to examine the categories and scope of legal safeguards provided to both buyers and sellers dealing with non-compliant items. Additionally, it aims to explore the responsibilities of corporate entities in addressing these issues within the realm of online commerce. In conducting this study, a normative legal research approach is utilized, which involves a qualitative analysis of existing legal norms within current laws and regulations. The research reveals two key aspects: 1) The safeguarding of consumers in instances where online transactions fail to meet agreed-upon terms, and 2) The examination of business actors' responsibilities to establish additional agreements with customers from the viewpoints of ITE UU and UUPK. Theoretical considerations suggest that contractual liabilities related to electronic transactions can render corporate actors accountable.